Case report: Donor-derived CLL-1 chimeric antigen receptor T-cell therapy for relapsed/refractory acute myeloid leukemia bridging to allogeneic hematopoietic stem cell transplantation after remission - Miao, Xiaojuan; Shuai, Yanrong; Han, Ying; Zhang, Nan; Liu, Yilan; Yao, Hao; Wang, Xiao; He, Guangcui; Chen, Dan; Fan, Fangyi; Chang, Alex H.; Su, Yi; et al. (Frontiers in Immunology, 2024)
Background: Explore the efficacy and safety of donor-derived CLL-1 chimeric antigen receptor T cell therapy (CAR-T) for relapsed/refractory acute myeloid leukemia (R/R AML) bridging to allogeneic hematopoietic stem cell transplantation (allo-HSCT) after remission. Case presentation: An adult R/R AML patient received an infusion of donor-derived CLL-1 CAR-T cells, and the conditioning regimen bridging to allo-HSCT was started immediately after remission on day 11 after CAR-T therapy upon transplantation. Then routine post-HSCT monitoring of blood counts, bone marrow (BM) morphology, flow cytometry, graft-versus-host disease (GVHD) manifestations, and chimerism status were performed. Result: After CAR-T therapy, cytokine release syndrome was grade 1. On day 11 after CAR-T therapy, the BM morphology reached complete remission (CR), and the conditioning regimen bridging to allo-HSCT started. Leukocyte engraftment, complete donor chimerism, and platelet engraftment were observed on days +18, +23, and +26 post-allo-HSCT, respectively. The BM morphology showed CR and flow cytometry turned negative on day +23. The patient is currently at 4 months post-allo-HSCT with BM morphology CR, negative flow cytometry, complete donor chimerism and no extramedullary relapse/GVHD. Conclusion: Donor-derived CLL-1 CAR-T is an effective and safe therapy for R/R AML, and immediate bridging to allo-HSCT after remission may better improve the long-term prognosis of R/R AML.